Customersâ€™ Purchase Intention of Green Cosmetics in India : Empirical Validations Using an Extended Theory of Planned Behavior (TPB) - Upadhyaya, Abhilasha Singh; Sijoria, Charu (Indian Journal of Marketing, 2024)
Purpose : The motive behind the present research was to examine the variables that influence consumersâ€™ intentions to purchase green cosmetics. Additionally, this research aimed to visualize the significance of green cosmetics in the thoughts of contemporary customers and examine current developments in the cosmetics sector. Design/Methodology/Approach : The proposed research framework was based on the theory of planned behavior, which is extended by introducing â€œEnvironmental Concernâ€ and â€œEnvironmental Knowledgeâ€ as the predictors of attitude toward the purchase intentions of green cosmetics. The empirical validations were achieved through multiple linear regression. A total of 286 responses were instrumented for the study. Findings : The findings of the study demonstrated that consumersâ€™ intentions to purchase green cosmetics are highly influenced by their attitudes about green cosmetics, perceived behavioral control, trust in green cosmetics, and social influence. Nevertheless, even when both variables had a considerable impact on customersâ€™ attitudes toward green cosmetics, environmental concern and environmental knowledge did not significantly affect consumersâ€™ intentions to purchase green cosmetics. Originality/Value : The study enriched the existing literature related to consumer purchase behavior of green cosmetics by picturing a holistic view of the existing academic literature available and also provided a scale for the purchase intention in the Indian context. Limitations : Though 286 responses were collected for the study, more responses could have altered the results. The sample size is the studyâ€™s limitation.